Overcoming Stress Through a Religious Psychology Approach - SITI RAHMA (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2019)
Stress is a natural bodily response to various life demands and pressures, which can have either positive or negative effects depending on how it is managed. This article explores the religious psychology approach as an effective strategy for managing stress through the integration of religious practices and spiritual values. Using a literature review method, the article establishes a theoretical4 foundation examining the relationship between stress, mental health, and religious strength. Findings indicate that acts of worship such as prayer, dhikr, and supplication play a significant role in reducing physiological and psychological stress levels by providing inner peace and social support. Furthermore, the internalization of spiritual values strengthens an individual's mental and emotional resilience. The integration of modern psychological concepts with religious spirituality offers a holistic approach that can enhance quality of life and mental well-being.